Quality characteristics of Arab and Terengganu roselles - Ding, Phebe; Wahab, Zakaria (2007)
Subjectively Arab and Terengganu roselle (Hibiscus sadbariffa L.) are different in terms of size, colour and taste. However, no objective measurement was reported. Therefore, objective measurement was carried out to determine the quality characteristics of Arab and Terengganu roselles. The colour of calyx and epicalyx, soluble solids concentration (SSC), titratable acidity (TA), pH, vitamin C contents and ratio of SSC/TA were determined. There was no significant differences in calyx L* values and malic acid percentage of Arab and Terengganu roselle. The calyx of Arab roselle showed significantly lower C* and h° values as compared to Terengganu roselle. The L*, C* and h° values of Arab roselle epicalyx was significantly lower than Terengganu. This result indicated that the epicalyx colour of Arab roselle is darker, less chroma and reddish-purple as compared to Terengganu. The SSC and SSc to TA ratio of Arab roselle were significantly higher than Terengganu roselle indicating Arab roselle was sweeter and more palatable than Terengganu. The pH value for Arab and Terengganu roselle was 2.62 and 2.68, respectively, where the pH value of Arab was significantly lower than Terengganu. The vitamin C content of Arab roselle was significantly higher then Terengganu. In conclusion, the subjective perception of Arab roselle as having sweeter taste, less sour and dark red as compared to Terengganu was not totally correct. The high SSC in Arab roselle renders the sour taste of roselle which actually has significantly lower pH value than Terengganu.